Habitat Suitability for Hoya spp. (Apocynaceae) in The Bodogol Conservation Area, West Java - Sulaeman, Masrayani; Sulistijorini, Sulistijorini; Rahayu, Sri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Hoya is a tropical flowering plant that has great potential as an export commodity. It needs to be cultivated to ensure its sustainability in nature. Information about the suitable habitat of Hoya was not widely known yet. This study aimed to compare the habitat characteristics of several species of Hoya. The research was conducted by exploring the sample plots determined by purposive sampling based on the differences of habitat characteristics. The biotic components observed were phorophyte species type and the number of individual of each Hoya species. The abiotic components measured in each plot were altitude and geographical position, air temperature, humidity, light intensity, wind speed, and canopy cover. Hoya ‘s diversity was analyzed using the Shannon Winner Index. Environmental factor data and biotic factors were analyzed with Canoco for Windows 4.5 software. There were 6 species of Hoya namely Hoya multiflora, Hoya imperialis, Hoya vitellinoides, Hoya hasseltii, Hoya campanulata and Hoya lacunosa found in this study. The highest biodiversity index was obtained in an altitude of 700-800 m.a.s.l (H’=1.41) and in hillsides area (H’=1.3). Hoya ‘s most frequent phorophyte was Schima wallichii. Factors affecting the presence of Hoya in the phorophytes were the position of attachment to the main stem and the rough surface characteristics of the tree. Hoya ‘s preference place was on the bark fracture. Abiotic factors that most influencing the existence of Hoya were air humidity and canopy cover. The data of this research can be used as basic information for carried out the conservation efforts and cultivation strategy in the future.